Prevalence of Anxiety and Depressive Symptoms among Hospitalized Patients Diagnosed with COVID-19 - Sharma, Sandipa; Gyawali, Siddinath; K.C., Niranjan; Sapkota, Subash; Shrestha, Siddhartha Kumar; Bataju, Pujan; K C, Rumi; Lamichhane, Ram Prashad (Journal of Nepal Health Research Council, 2024)
Background: A series of acute, atypical respiratory diseases was identified in Wuhan, China, which was named Coronavirus disease (COVID-19) by the World Health Organization (WHO), and the disease was later declared a pandemic. This disease has psychological effects in addition to physiological symptoms. This study aims to find out the psychological impacts of disease in the form of anxiety and depressive symptoms among hospitalized patients diagnosed with COVID-19. Methods: A multicentric descriptive cross-sectional study was conducted among patients diagnosed with COVID-19 who were admitted from July 1, 2021 to August 15, 2021 in six different hospitals. Ethical approval was obtained from the Nepal Health Research Council (reference number 284). COVID-19 was diagnosed using Reverse Transcription Polymerase Chain Reaction (RT-PCR) or COVID-19 antigen test. Data were collected from the patients using proforma containing the demographic profile and two questionnaires (Hospital Anxiety and Depression scale and Global Health Questionnaire-12) translated into the Nepali language. Results: Among 360 patients who participated in the study, 194 (53.9%) were males and 166 (46%) were females. Symptoms of anxiety and depression were seen in 161 (44.7%) and 253 (70.3%) of the participants respectively. Similarly 349 (96.9%) of them were found to have clinically significant mental distress. Conclusions: The prevalence of anxiety and depressive symptoms among hospitalized patients diagnosed with COVID-19 is significantly high compared to the general population. Keywords: Anxiety; coronavirus disease-2019; cross-sectional study; depression; psychological effect.